The Effect Of Innovation Strategy In The Influence Of Managerial Ability On Firm Performance - Khairanis Yulita; Zaenal Fanani (Universitas Muhammadiyah Malang, 2021)
Managerial ability collaborates managerial skill and effort to improve firm performance through resources utilization and strategy implementation. This study is aimed to examine the influence of managerial ability on firm performance with the mediation effect of innovation strategy. The final sample is 940 firms from the manufacturing sector listed on the Indonesian Stock Exchange 2012-2019. Analysis techniques use Data Envelopment Analysis (DEA) to measure managerial ability score, cluster analysis to analyze company strategy, and path analysis to test and analyze variables statistically. The result shows that innovation strategy does not mediate the influence of managerial ability on firm performance. Higher managerial ability directly increases the firm performance, but it decreases innovation strategy and innovation strategy does not affect firm performance. In conclusion, managers should choose between efficiency and innovation because it is a trade-off. Therefore, the company must sacrifice one of them.